PRINCIPAL'S STRATEGY IN DEVELOPING ENTREPRENEURSHIP IN ELEMENTARY SCHOOLS (Lembaga Pengembangan Kinerja Dosen, 2022)
Education has become the center of transformation in the social, economic, and political fields and has become an integrative force in people's lives. Entrepreneurship must be given as early as possible so that what is a concern in society against graduates from an educational institution, namely unemployment, can be eliminated. Therefore, the principal as a person who has entrepreneurial policies and competencies must be able to develop entrepreneurship well. This research uses a quantitative approach with a case study type. This research was conducted at Madrasah Tsanawiyah Negeri 1 Paiton Probolinggo. The selection of the research location is based on the consideration that the researcher is easy to get information and the location is a madrasa that implements the Information technology class and the adiwiyata program in Paiton. The informants in this study were the principal, teachers and students. Techniques in data collection used participant observation, in-depth interviews and documentation studies. Data analysis used is data reduction, data presentation, and conclusion drawing. The principal's strategy in developing entrepreneurship is done with three strategies, namely formulation strategy, implementation strategy, and evaluation strategy.